2020
DOI: 10.1038/s42255-019-0157-1
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 directly inhibits AMPK to promote cell proliferation under nutrient stress

Abstract: Central to cellular metabolism and cell proliferation are highly conserved signalling pathways controlled by mammalian target of rapamycin (mTOR) and AMP-activated protein kinase (AMPK) 1 , 2 , dysregulation of which are implicated in pathogenesis of major human diseases such as cancer and type 2 diabetes. AMPK pathways leading to reduced cell proliferation are well established and, in part, act through inhibition of TOR complex-1 (TORC1) activity. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 40 publications
5
94
1
Order By: Relevance
“…4. The crosstalk between these signaling pathways can occur through the direct reciprocal antagonism, such as between mTORC1 and AMPK 190,207,242 or Akt and LKB1, 187 or via indirect inhibition of downstream signaling effectors. For example, the ULK1 complex, which promotes autophagy, is inhibited and activated by mTORC1 and AMPK signaling, respectively.…”
Section: Immunometabolic Signaling Networkmentioning
confidence: 99%
“…4. The crosstalk between these signaling pathways can occur through the direct reciprocal antagonism, such as between mTORC1 and AMPK 190,207,242 or Akt and LKB1, 187 or via indirect inhibition of downstream signaling effectors. For example, the ULK1 complex, which promotes autophagy, is inhibited and activated by mTORC1 and AMPK signaling, respectively.…”
Section: Immunometabolic Signaling Networkmentioning
confidence: 99%
“…This lipotoxicity was associated with a sustained mTOR activation, but the association with AMPK was not explored. Excessive fat also induces constitutive activation of mTORC1 that directly inhibits AMPK activity, suggesting a link between mTOR and AMPK [156,157]. However, AMPK-mediated activation of autophagy protects against renal injury, particularly in AKI [158].…”
Section: Ampk and The Regulation Of Renal Autophagy And Mitophagymentioning
confidence: 99%
“…In support of this notion, Aster‐C deficiency also led to accumulation of LC3‐II during starvation (Fig EV2C). A recent study demonstrated that mTORC1 directly inhibits AMPK signaling (Ling et al , ). Consistent with the hyper‐activation of mTORC1 in Aster‐C KO cells, the phosphorylation level of ULK1 at S555, a key phosphorylation site by AMPK (Egan et al , ,b), is significantly lower in Aster‐C KO cells during nutrient starvation (Fig EV2C).…”
Section: Resultsmentioning
confidence: 99%